Development of Vehicle Lighting System Using LED Application - Ponniran, Asmarashid; Mat Sor, Azila Nor Azrani; Joret, Ariffuddin; Munir, Handy Ali (International Journal of Integrated Engineering, 2011)
A Light Emitting Diode (LED) is a semiconductor device which converts electricity into light. LEDs are preferred over incandescent lamps because of their long life and their availability in various colors and brightness levels. The aim of this paper is to present the development of vehicle lighting system using LED application. In this system, high power LEDs type is chosen as automobile headlight model and controller circuit using microcontroller is considered. The LEDs are driven using buck converter circuit with appropriate Pulse Width Modulation (PWM) signal whereby the PWM signals are generated by microcontroller. The system is divided into 2 modes of operation, manual and automatic. The automatic mode of operation will be operating when the LDR senses the level of light brightness whereby the level of brightness is proportion to duty cycle of PWM. Meanwhile, for the manual mode of operation, 3 switches which are SW2 with 20% duty cycle, SW3 with 40% duty cycle and SW3 with 80% duty cycle are developed. The result shows that the maximum brightness of LED is about 127.6 Lumen at 80% of duty cycle for manual operation mode. Besides, by varying theduty cycle of PWM signal for both modes of operation, manual and automatic, LED brightness can be controlled.